O poeta ensina a ousar: ironia e didatismo nas Epístolas de Horácio - Bruno Francisco dos Santos Maciel (2017)
Horaces Epistles (1st century BCE) are divided into two books. The first one, composed of twenty letters, is filled with scenes of recte uiuere (to live correctly). The second one, with its three letters (among them the Art of Poetry), deals mainly with issues of recte scribere (to write correctly). For this reason, they are usually read separately. In this dissertation, we propose an approach in which all the epistles are read as a whole. At the base and the horizon of our reading, there is the assumption that exists an ambiguous poetic game (ludus) between irony and didacticism, which, conceived more as discursive strategies present throughout the corpus, are its unifying element. Thus, the three subjects dealt with in a more frontal way are presented and analyzed: the metapoeticity of prosaic poems from the first book, contrasted with that from the second one; the poeta uesanus (mad poet); and the poetic persona of Horace himself. Besides, it is the ambivalence of this ludus in whose bosom, in a sometimes philosophical, sometimes poetic thematic framework, we can see both an ironic didacticism and a didactic (self-)irony that brings us to a productive intermixture between recte uiuere and recte scribere. At the end, we also present a translation of the Epistles.